Les petits bronzes du mont d’Uzore (Loire) : un désir d’Antiquité - Jean-Claude Béal (Revue Archéologique du Centre de la France)
Discovered about 1867 in Saint-Paul-d’Uzore (Loire), three bronze statuettes featuring Mercury, Harpocrates and an unknown god, are now part of the collections of the Museum of Diana in Montbrison. The iconographic Mercury type is very unusual for the area, and the other two figurines have characteristics that tempt us to view them as fakes, contrary to what was believed until now. Burial of these three items could be the work of a forger who wanted to support the theory of a mountain of Uzore dedicated to Isis.